3D inkjet-printed UV-curable inks for multi-functional electromagnetic applications - Saleh, Ehab; Woolliams, Peter; Clarke, Bob; Gregory, Andrew; Greedy, Steve; Smartt, Chris; Wildman, Ricky D.; Ashcroft, Ian; Hague, Richard J.M.; Dickens, Phill; Tuck, Christopher (Elsevier, 2017)
Inkjet printing of multiple materials is usually processed in multiple steps due to various jetting and curing/sintering conditions. In this paper we report on the development of all inkjet-printed UV-curable electromagnetic responsive inks in a single process, and the electromagnetic characterization of the developed structure. The ink consists of iron oxide (Fe3O4) nanoparticles (nominal particle size 50–100 nm) suspended within a UV curable matrix resin. The viscosity and surface tension of the inks were tuned to sit within the inkjet printability range.